The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1984
DOI: 10.1128/aac.26.6.793
|View full text |Cite
|
Sign up to set email alerts
|

Experimental evaluation of chlorhexidine gluconate for ocular antisepsis

Abstract: Chlorhexidine gluconate is a bisguanide germicide currently available with 70% isopropanol (Hibistat, Hibitane) or a detergent (Hibiclens, Hibiscrub) for preoperative skin preparation. As these solvents are toxic to the cornea, we investigated the safety and efficacy of aqueous chlorhexidine solutions for ophthalmic use. Chlorhexidine in Tris-glycine buffer was evaluated for retardation of epithelial regeneration after experimental corneal abrasion in rabbits. Irrigant concentrations of 2.0 and 4.0% chlorhexid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0
2

Year Published

1993
1993
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(32 citation statements)
references
References 12 publications
(11 reference statements)
1
29
0
2
Order By: Relevance
“…Thereby, the textile napkin virtually serves as a sustained release reservoir of CHG during phacoemulsification. Moreover, equal diameter of the growth inhibition zones before and after phacoemulsification cataract extraction also indicates that 0.5% levofloxacin ophthalmic solution instilled preoperatively is not an antagonist of 0.02% CHG. Additionally, antimicrobial activity of both unused textile napkins and used textile napkins, wetted with 0.02% CHG against gram-positive bacteria is more than gram-negative (Table 1), that is comparable to certain reports [5,20]. Since microbial flora under the textile napkins mixed with flora of the conjunctival sac and the lid margin, the result of microbial culture from the conjunctival sac after withdrawing the textile napkins on completion of the surgery is disputed.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Thereby, the textile napkin virtually serves as a sustained release reservoir of CHG during phacoemulsification. Moreover, equal diameter of the growth inhibition zones before and after phacoemulsification cataract extraction also indicates that 0.5% levofloxacin ophthalmic solution instilled preoperatively is not an antagonist of 0.02% CHG. Additionally, antimicrobial activity of both unused textile napkins and used textile napkins, wetted with 0.02% CHG against gram-positive bacteria is more than gram-negative (Table 1), that is comparable to certain reports [5,20]. Since microbial flora under the textile napkins mixed with flora of the conjunctival sac and the lid margin, the result of microbial culture from the conjunctival sac after withdrawing the textile napkins on completion of the surgery is disputed.…”
Section: Discussionsupporting
confidence: 52%
“…Firstly, 0.02% CHG is the most stable within the pH range 5 to 8 [5], in the pH range of 0.5% levofloxacin ophthalmic solution [19]. Secondly, Staphylococcus aureus, Staphylococcus epidermidis, Bacillus subtilis, Streptococcus pyogenes, Micrococcus sp., Escherichia coli, Enterobacter aerogenes and Pseudomonas aeruginosa are sensitive to it [20] and lastly, methicillin-resistant Staphylococcus aureus exhibits low-level resistance to chlorhexidine [21]. Additionally, as conducted research reveal, CHG as a cationic molecule [5] binds to negatively charged cells of the oral cavity.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, another recent retrospective case series of 4,322 IVI exclusively performed under chlorhexidine gluconate antisepsis presented an EO rate of 0.023% [95], which is comparable to EO rates using PI [67]. However, alcoholic chlorhexidine bears a potential toxic risk on the cornea, yet aqueous chlorhexidine is considered an alternative in patients with local irritation or allergy to PI components [96]. …”
Section: Peri- /Injection Management In Intravitreal Pharmacotherapymentioning
confidence: 99%
“…Currently, the most widely used antiseptics are povidone-iodine solution and chlorhexidine solution [1, 2]. However, these antiseptics have various disadvantages.…”
Section: Introductionmentioning
confidence: 99%
“…Hanasaki [5, 6]reported that more than half of patients showed moderate or severe corneal epithelial defects due to ocular surface disinfection prior to surgery with 1.25% povidone-iodine solution. Chlorhexidine is another antiseptic for ocular surfaces, but this compound is also toxic for the cornea [2]. Therefore, an alternative antiseptic with a wider antimicrobial spectrum and less propensity to irritate corneal tissue has been sought.…”
Section: Introductionmentioning
confidence: 99%